THE RELATIONSHIPS OF WORK ENVIRONMENT, ATTITUDE TOWARD TEACHING PROFESSION, AND PERFORMANCE OF TEACHERS IN PUBLIC HIGH SCHOOLS IN LOMBOK BARAT - Yudin Citriadin; Bambang Budi Wiyono; Muhammad Huda AY; Imron Arifin (AIBPM Publisher, 2019)
This study is aimed to acknowledge the relationship between work environment, attitude toward teaching profession, and teachers’ performance. The approach used in this study is a quantitative approach. The research sample includes the teachers of public high schools in Lombok Barat District as many as 134 individuals. The statistical analysis was conducted using structural equation modeling (SEM). The findings show that the attitude toward teacher profession directly affects the work environment and teachers; performance while the work environment does not affect the teachers’ performance. The significance of this study is for the Department of Education and Culture of Lombok Barat District and the headmasters, to be utilized as the foundation and consideration of policymaking and facilitating the teachers to improve their performance.